2013
DOI: 10.5370/jicee.2013.3.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Metal Hydride Tank Structure on the Reaction Heat Recovery for the Totalized Hydrogen Energy Utilization System

Abstract: A Totalized Hydrogen Energy Utilization System (THEUS) is proposed for load leveling and stabilizing the grid. The THEUS is a novel unitized regenerative fuel cell system that achieves high overall efficiency through optimized heat utilization. In this paper, a metal hydride tank (MHT) is chosen as hydrogen storage. In the MHT, the heating and cooling from adsorption/desorption processes is used to produced heated and chilled water for building ventilation systems. A new horizontal type MHT was developed to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…After the first absorption process, the reaction heat recovery rates decreased as compared with the results in the individual absorption-desorption test because a part of the reaction heat was consumed in the heating or cooling of the metal hydride material and the stainless-steel tank. Even if the operating pressure range was different, it could be confirmed that the heat recovery ability was almost the same as that of the metal hydride tank at SRNL [16].…”
Section: Results For the Individual Absorption-desorption Testsupporting
confidence: 57%
“…After the first absorption process, the reaction heat recovery rates decreased as compared with the results in the individual absorption-desorption test because a part of the reaction heat was consumed in the heating or cooling of the metal hydride material and the stainless-steel tank. Even if the operating pressure range was different, it could be confirmed that the heat recovery ability was almost the same as that of the metal hydride tank at SRNL [16].…”
Section: Results For the Individual Absorption-desorption Testsupporting
confidence: 57%